Зміни електричної активності серця та його вегетативної регуляції у молодих хворих на рак щитоподібної залози у поопераційний період на тлі супресивної терапії залежно від терміну її застосування - Зубкова, С. Т. (Clinical Endocrinology and Endocrine Surgery, 2011)
Effect of suppressive L-thyroxin therapy on the state of heart electrical activity and its vegetative regulation in young patients who were operated for thyroid cancer in different periods of postoperative treatment (in 2-6 and 12-18 months, 2-5 and 5-9 years) was studied. Using the daily ECG-monitoring the appearance of myocardial electric instability manifested by an increase in average daily and nightly frequency of the systole, more frequent episodes of tachyarrhythmia and extrasystole was revealed. These changes were associated with changes in vegetative regulation of the heart rate, and QTc prolongation. Frequency of obtained changes is dependent on suppressive L-thyroxin therapy course.